âAZL (COITUS INTERRUPTUS) DALAM PANDANGAN FUKAHA - Ahmad, La Ode Ismail (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2010)
This article copes with the issue of âazl from Islamic perspective. Generally, âazl is the prevention of pregnancy by releasing the sperm out of vagina. In modern context, this practise is analogous with the family planning. The only difference is that the modern family planning uses medicines. Islamic scholars, basing their respective arguments on some hadits of the prophet, have different opinion on the issue: some of them permit the practise of âazl, while some others prohibit it. This study reveals that the hadits used by Islamic scholars who forbid the practise of âazl is dhaâif. Therefore, the practise of âazl is actually permitted, with the permission of wife, and without permission if applied to slave.